Pengaruh citra destinasi, fasilitas, dan presepsi harga terhadap minat berkunjung wisatawan ke objek wisata pantai di Kabupaten Jepara - Sukardi, Agung Slamet; Afidah, Elvira Ulil (Nur Science Institute, 2024)
Many factors, including destination image, facilities, and price perceptions, influence tourists' interest in visiting. Tourist destinations give a good impression, good facilities, and reasonable prices, increasing tourists' interest in coming to that place. This research examines the influence of destination image, facilities, and price perceptions on interest in visiting tourism in Jepara Regency. Data collection used the accidental sampling method, which resulted in 97 respondents. Multiple linear regression analysis was used to test the objectives of this research. The research results show no influence between destination image and price perception on tourists' interest in visiting beach tourist attractions in Jepara Regency. Meanwhile, facilities influence tourists' interest in visiting. Simultaneous results of destination image, facilities, and price perception influence tourist interest in visiting beach tourist attractions in Jepara Regency